Historia wsi gniazdowej Olszowskich h. Wilczekosy: The history of the Olszowscy nesting village of the Wilczekosy coat of arms - Pakowski, Zdzisław (Prace Polonistyczne, 2019)
The first written record of Olszowa, a village in Brzeziny district of Łęczyca province, comes from A.D. 1379. In the early XV century the village was owned by the Bielinas of Wola Drzazgowa and it is the family seat of the Olszowski family of Prus II (Wilczekosy – Wolfscythes) coat of arms, originating from the nearby village of Gutków. The Olszowski’s were descendants of Prussian settlers, and descendants include the Primate Andrzej Olszowski. The property of the Olszowskis, in Olszowa dates from 1445 to 1824 i.e. almost 400 years. Since 1824 the ownership of Olszowa property is well documented in mortgage registers. Important people that lived in and owned Olszowa include Ludwik Szweycer and his son Wincenty – a January Uprising volunteer, Wiktoria Lewińska, a sister of Narcyza Żmichowska – a writer and feminist, and her son Ludwik Lewiński – also a January Uprising volunteer, professor Kazimierz Glinka-Janczewski, a forester, university professor and popularizer of forestry, and finally the Malcz family: Julian and his sons Bolesław – landowner and social activist, and Władysław – head of division of Warsaw firefighters and Lucjan – sublieutenant of the “Bayonnais”, who fell at the Western Front of the Great War.